Exploring The Impact of Depression Among C&S Engineer at Construction Industry - Phang Jun Liang; Hasmori, Muhammad Fikri (Journal of Structural Monitoring and Built Environment, 2025)
This study investigates the prevalence, contributing factors, and impact of depression among civil and structural (C&S) engineers within Sarawak’s construction industry. Depression, a critical mental health concern, is closely associated with diminished workplace safety performance, productivity, and overall well-being. Data were collected from 220 respondents through structured surveys, incorporating instruments such as the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) and Likert-scale assessments. The data were analyzed using descriptive statistics, correlation analysis, and regression techniques. The results indicate that multitasking demands, tight project deadlines, and physical fatigue are major contributors to depression, which was primarily reported at mild to moderate levels. Regression analysis revealed a strong relationship between depression and safety performance, with depression accounting for 95.9% of the observed variability. Additionally, symptoms like mental fatigue and musculoskeletal discomfort compound workplace challenges. These findings underscore the urgent need for targeted mental health support, ergonomic interventions, and policy reforms to enhance both employee well-being and safety outcomes in the construction sector.